Normative Scores for the NIH Toolbox Dynamic Visual Acuity Test from 3 to 85 Years - Li, Carol; Beaumont, Jennifer L.; Rine, Rose Marie; Slotkin, Jerry; Schubert, Michael C. (Frontiers in Neurology, 2014)
As part of the National Institutes of Health Toolbox initiative, a computerized test of dynamic visual acuity (cDVA) was developed and validated as an easy-to-administer, cost- and time-efficient test of vestibular and visual function. To establish normative reference values, 3,992 individuals, aged 3–85 years, without vestibular pathology underwent cDVA testing at multiple clinical research testing facilities across the United States. Test scores were stratified by sociodemographic characteristics. cDVA was worse in males (p < 0.001) and those subjects 50 years or older, while there was no difference in dynamic visual acuity across age groups binned from 3 to 49 years. Furthermore, we used these normative cDVA data as a criterion reference to compare both the long (validated) and short versions of the test. Both versions can distinguish between those with and without vestibular pathology (p = 0.0002 long; p = 0.0025 short). The intraclass correlation coefficient between long- and short-cDVA tests was 0.86.